2020
DOI: 10.1002/mrm.28433
|View full text |Cite
|
Sign up to set email alerts
|

Relayed nuclear Overhauser enhancement imaging with magnetization transfer contrast suppression at 3 T

Abstract: Purpose: To develop a pulsed CEST magnetization-transfer method for rapidly acquiring relayed nuclear Overhauser enhancement (rNOE)-weighted images with magnetic transfer contrast (MTC) suppression at clinical field strength (3 T). Methods: Using a pulsed CEST magnetization-transfer method with low saturation powers (B 1) and long mixing time (t mix) to suppress contributions due to strong MTC from solid-like macromolecules, a low B 1 also minimized direct water saturation. These MTC contributions were further… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 53 publications
1
27
0
Order By: Relevance
“…With fixed TR, the number of lines per blade determines the mixing time between saturation pulses, following τitalicmix=TR×#linesperblade. Previous pulsed CEST optimization has already demonstrated that 1 pulse width larger than 40 ms would achieve enough frequency selectivity at 3T 49 . Hence, the pulse width of the sinc‐gauss saturation pulses was set to 50 ms. For the human brain study, images were acquired at 5 × 3 × 3 mm 3 resolution using 15 slices and a FOV of 220 × 220 mm 2 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…With fixed TR, the number of lines per blade determines the mixing time between saturation pulses, following τitalicmix=TR×#linesperblade. Previous pulsed CEST optimization has already demonstrated that 1 pulse width larger than 40 ms would achieve enough frequency selectivity at 3T 49 . Hence, the pulse width of the sinc‐gauss saturation pulses was set to 50 ms. For the human brain study, images were acquired at 5 × 3 × 3 mm 3 resolution using 15 slices and a FOV of 220 × 220 mm 2 .…”
Section: Methodsmentioning
confidence: 99%
“…Previous pulsed CEST optimization has already demonstrated that 1 pulse width larger than 40 ms would achieve enough frequency selectivity at 3T. 49 Hence, the pulse width of the sinc-gauss saturation pulses was set to 50 ms. For the human brain study, images were acquired at 5 × 3 × 3 mm 3 resolution using 15 slices and a FOV of 220 × 220 mm 2 . The image matrix was resized to 96 × 96 during reconstruction.…”
Section: Mri Experimentsmentioning
confidence: 99%
“…Pulsed-CEST sequence was set up for rNOE imaging by modifying the turbo spin echo (TSE) sequence. The saturation parameters optimized in previous study on a preclinical 3T MRI scanner were applied here ( Huang et al, 2021a ). Briefly, the saturation module contained a pulse train with a saturation power (B 1 ) of 0.8 μT, a pulse duration (t p ) of 40 ms, a mixing time (t mix ) of 60 ms and a pulse number (N) of 10.…”
Section: Methodsmentioning
confidence: 99%
“…rNOE imaging has high specificity towards mobile proteins and lipids and thus holds the potential to detect myelin change in MS brain, as myelin consists of abundant lipids and proteins ( Baumann and Pham-Dinh, 2001 ). MT contrast and direct water saturation (DS) are two major contaminations in rNOE contrast especially at clinical field strengths (such as 3T) ( Huang et al, 2021a , Xu et al, 2016 ). Recently, we developed a rNOE imaging scheme with MT suppression using an optimized pulsed-CEST sequence, i.e.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation